2011
DOI: 10.1093/dnares/dsr011
|View full text |Cite
|
Sign up to set email alerts
|

In silico Analysis of 3'-End-Processing Signals in Aspergillus oryzae Using Expressed Sequence Tags and Genomic Sequencing Data

Abstract: To investigate 3′-end-processing signals in Aspergillus oryzae, we created a nucleotide sequence data set of the 3′-untranslated region (3′ UTR) plus 100 nucleotides (nt) sequence downstream of the poly(A) site using A. oryzae expressed sequence tags and genomic sequencing data. This data set comprised 1065 sequences derived from 1042 unique genes. The average 3′ UTR length in A. oryzae was 241 nt, which is greater than that in yeast but similar to that in plants. The 3′ UTR and 100 nt sequence downstream of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Interestingly, AATGAA always ranks second for all strand-specific data sets in S. pombe. This motif ranks as the highest NUE motif in Aspergillus oryzae (Tanaka et al 2011), emphasizing the evolutionary conservation of the PAS sequence motifs across some organisms. However, the mutation of AATAAA to AATGAA can lead to loss of PAS function in humans (Bennett et al 2001).…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, AATGAA always ranks second for all strand-specific data sets in S. pombe. This motif ranks as the highest NUE motif in Aspergillus oryzae (Tanaka et al 2011), emphasizing the evolutionary conservation of the PAS sequence motifs across some organisms. However, the mutation of AATAAA to AATGAA can lead to loss of PAS function in humans (Bennett et al 2001).…”
Section: Discussionmentioning
confidence: 87%
“…In the 3′UTR regions, there is predominance of AT/AT (gymnosperms) and AAT/ATT (both taxa), which are not the target for methylation [62]. An increased content in A + T nucleotides in the 3′UTR fraction has been reported before in vertebrates [63], mammals [64], yeast [65] and Arabidopsis [4], which seems to be related to the UTR processing signal composition.…”
Section: Discussionmentioning
confidence: 91%
“…Analysis of genes in humans and rats have shown that the 3′ region of genes can be dynamically altered by TEs during evolution, which suggests that TEs can provide alternative polyadenylation sites when inserted downstream of endogenous genes [ 40 ]. However, the only analysis of polyadenylation sites in fungi has been performed in Aspergillus oryzae [ 41 ]. Therefore, because of the current lack of knowledge about the 3′ gene regulatory regions of fungi, additional studies are necessary to measure the possible involvement of TEs in the evolution of the 3′ ends of genes.…”
Section: Discussionmentioning
confidence: 99%